Multiple-dose pharmacokinetics of peginterferon alfa-2b in patients with renal insufficiency - Gupta, Samir K (Blackwell Science Inc, 2007)
AIM: To evaluate the safety, tolerability and multiple-dose pharmacokinetics of pegylated interferon (PEG-IFN) alfa-2b in patients with moderate or severe renal insufficiency and in those with normal renal function. METHODS: In an open-label study, subjects with normal renal function (creatinine clearance >80 ml min(−1) per 1.73 m(2)) and patients with moderate (30–50 ml min(−1) per 1.73 m(2)) or severe (10–29 ml(−1) min(−1) per 1.73 m(2)) renal impairment received weekly injections of PEG-IFN alfa-2b (1.0 µg kg(−1)) for 4 weeks. Safety assessments were made before each injection and blood samples were taken up to 168 h after the final dose. RESULTS: Renal insufficiency increased PEG-IFN alfa-2b exposure. Area under the curve for 0–τ (dosing interval of 168 h), AUC(τ), was increased 30% and 120% in patients with moderate or severe renal insufficiency, respectively. Mean maximum serum concentration was almost doubled in patients with severe insufficiency [1305.8 pg ml(−1); 95% confidence interval (CI) 825, 1786] compared with subjects with normal renal function (731.4 pg ml(−1); 95% CI 407, 1056), whereas the apparent volume of distribution was reduced (0.80 l kg(−1)vs. 1.28 l kg(−1), respectively). Elimination half-life was extended in patients with moderate and severe renal insufficiency (65.6 h and 64.9 h, respectively) compared with subjects with normal renal function (51.5 h). Significant differences were observed in the AUC and C(max) values of patients with severe renal dysfunction, compared with those who had normal renal function (P< 0.05; Kruskal–Wallis test). PEG-IFN alfa-2b was well tolerated and adverse events were similar in both treatment groups. CONCLUSIONS: Exposure to PEG-IFN alfa-2b is increased in patients with renal insufficiency, suggesting that doses of the drug should be reduced by 50% in patients with severe renal insufficiency and by 25% in those with moderate insufficiency.